Analisis Kriminologis Terhadap Faktor Penyebab Tindak Pidana Korupsi Di Sektor Publik - Ramdani, Rahmat Memo; Henny Yuningsih (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Corruption in the public sector is a serious legal and social issue, potentially damaging the integrity of the government, hindering development, and reducing public trust in state institutions. Corruption Not Only Harms the State, But Also Affects Social Justice and Destroys Social Order Through the Culture of Nepotism and Collusion. In the Perspective of Criminology, the Criminogenic Factors that Encourage Corruption Can Be Seen from Personal, Organizational and Structural, Economic, Cultural, and Social Factors. Corruption also hinders the allocation of resources for development that should improve the welfare of the community, such as education, health, and infrastructure. Therefore, combating corruption must be carried out through a comprehensive approach, including bureaucratic reforms to enhance transparency and accountability, as well as changes in organizational culture that support integrity and ethics. Through these steps, it is hoped that a more transparent, efficient, and fair public sector will be created, which in turn will improve development and restore public trust in the government.